Beyond polarization towards dynamic balance: harmony as the core of mental health - Delle Fave, Antonella; Wissing, Marié Philipina; Brdar, Ingrid (Frontiers in Psychology, 2023)
Worldviews are culturally derived assumptions that influence individual and collective behaviors, values, and representations of reality. The study of mental functions is not exempt from this influence, as reflected in scientific theories, methodological approaches, and empirical studies. Despite acknowledging the interplay of mental processes with developmental, environmental, and cultural dimensions, psychological research is still primarily based on quantitative methods, and on the conceptualization of mental phenomena as unfolding along polarized continua. A lively epistemological debate surrounds this approach, especially underscoring the risk of blurring the distinction between constructs derived from statistical models and real-life processes and experiences. Based on this debate and on recent empirical evidence derived from the positive psychology literature, this paper is aimed at proposing an integrated view of mental health, as a holistically patterned, contextually imbedded, and dynamic phenomenon changing over time and across life events, with harmony, harmonization and dynamic balance as core qualities. The heuristic potential of investigating the qualitative configuration patterns of mental health dimensions across individuals and groups, beyond their position along a quantitative continuum, is outlined. The development of more integrated approaches and methodologies to investigate mental health as a harmonization process, taking into account personal, contextual and developmental features, would be aligned with evidence derived from the integration of traditional nomothetic and ideographic approaches, and other life sciences. However, the development of a transdisciplinary line of research requires further inputs from different epistemological views, as well as higher attention to the potential contribution of different philosophical traditions.